New Grounded Feminist Approach to Islam in Indonesia: A Textual Analysis of Rahima and Fahmina’s Publications - Nina Nurmila (Journal of Asian Social Science Research, 2020)
This article aims to offer a textual analysis of Rahima and Fahmina’s publications. Rahima and Fahmina are two Non-Government Organizations founded in 2000 by a young generation of Nahdlatul Ulama (NU), one of the largest moderate Muslim organizations in Indonesia. There are more similarities than differences between Rahima and Fahmina because the persons involved in the organizations are close friends and, in fact, the same persons even though both are based in two different cities. Since their foundation, both Rahima and Fahmina have published many books and magazines. This article argues that both Rahima dan Fahmina publications offer a new grounded feminist approach to Islam, which counterbalance the dominant male-biased normative approach to Islam in most Muslim societies. These publications are based on their feminist activism and community engagement with the grass-root level of many Nahdlatul Ulama pesantrens (Islamic boarding schools). The topics of their publication cover many current issues such as fiqh of women’s reproductive rights and empowerment, fiqh of the daily life of migrant workers, fiqh of anti-trafficking, prevention of child marriage, violent extremism and religious pluralism. As a result, the progressive nature of their publications negates the existing label of NU as the traditionalist organization.